Prophetic Guidance in Selling and Its Impact on Society - Ahamed, Malik Dianoor (Journal of Islamic Sciences, 2020)
The study aimed to identify the prophetic guidance in sales and its impact on the Islamic society, by clarifying the concept of sales and legitimacy, provisions and ethics, and to urge permissible earning “halal” and warn of the sale prohibited as stated in the Prophet's guidance. the study followed the inductive analytical approach, The study dealt with legitimate sales and its impact on the stability and security of societies. It also showed the types of prohibited sales and their negative impact on Islamic society. The study focused on some sales in terms of legitimacy and lack thereof in accordance with the Prophet's Sunnah, the study also stressed the importance of the jurisprudence of sales in the educational and community institutions, and urged people to understand and apply it and warn of its ignorance, the study recommended doctrinal courses especially the jurisprudence of sales and the printing of jurisprudence of sales introductory papers to dealers and the general public.
Keywords: Prophet's Guidance; Selling; Islamic Jurisprudence; Society